Persentase perbandingan bahan bakar campuran cangkang dan fiber kelapa sawit terhadap unjuk kerja boiler di PKS PTPN V sei galuh - Sri Andriansyah Andri; Rafil Arizona (Jurnal Teknik Mesin Indonesia, 2023)
This study discusses the percentage comparison of fiber and palm shell fuel mixtures by having several different percentages, so that the best percentage of fuel for boiler performance is obtained. In this case the calorific value of the fuel plays an important role in determining the efficiency of the boiler, where the higher the calorific value, the less fuel is used. So that it greatly affects the performance of the boiler and is more economical in saving fuel. Retrieval of boiler data at PKS PTPN V Sei Galuh. In the form of fuel composition and boiler unit parameters obtained using water and steam properties software which is then carried out research to find the best percentage of boiler fuel. Based on the results of the research that has been done, the best results are obtained at the percentage of 75% fiber fuel and 25% palm shell with 86% efficiency, fuel consumption of 759 kg/hour, boiler capacity of 40.091,8 kg/hour, consumption combustion air of 8.500,401 kg.air/kg.fuel, and the heat generated is 23.213.235,24 kcal/hour or 23.21×106 kcal/hour. With the results of this study, the boiler can produce electrical energy of ± 1 Megawatt with electricity requirements to run the entire performance of the machine for one day of ± 0,8 Megawatts.